2019
DOI: 10.1371/journal.pone.0224215
|View full text |Cite
|
Sign up to set email alerts
|

‘We are all serving the same Ugandans’: A nationwide mixed-methods evaluation of private sector surgical capacity in Uganda

Abstract: IntroductionHalf of all Ugandans (49%) turn to the private or private-not-for-profit (PNFP) sectors when faced with illness, yet little is known about the capacity of these sectors to deliver surgical services. We partnered with the Ministry of Health to conduct a nationwide mixed-methods evaluation of private and PNFP surgical capacity in Uganda.MethodsA standardized validated facility assessment tool was utilized to assess facility infrastructure, service delivery, workforce, information management, and fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…For example, the highest reported availability was in a study of private and public facilities in Uganda which showed that 15 of 16 facilities had access to oxygen at least half of the time. However, six of those hospitals lacked access to oxygen more than 25% of the time and one hospital never had access to oxygen [ 14 ]. The availability of pulse oximetry was significantly more limited, ranging from 0%-64% of facilities assessed [ 20 , 27 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the highest reported availability was in a study of private and public facilities in Uganda which showed that 15 of 16 facilities had access to oxygen at least half of the time. However, six of those hospitals lacked access to oxygen more than 25% of the time and one hospital never had access to oxygen [ 14 ]. The availability of pulse oximetry was significantly more limited, ranging from 0%-64% of facilities assessed [ 20 , 27 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that while facilities may have oxygen available, their ability to accurately identify patients who may need oxygen and titrate the amount delivered appropriately is limited. These limitations are especially true for public facilities and those providing lower tiers of care [ 13 , 14 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…In sub-Saharan Africa, unreliable or inaccurate diagnostic testing has been shown to increase unnecessary system expenditures and lead to life-threatening misdiagnoses or delays in treatment [5] . In Uganda, a large portion of private hospitals providing surgical care do not have access to blood [37] . Furthermore, despite having less surgical volume than public hospitals, private facilities were often better equipped than public ones [37] .…”
Section: Discussionmentioning
confidence: 99%
“…In Uganda, a large portion of private hospitals providing surgical care do not have access to blood [37] . Furthermore, despite having less surgical volume than public hospitals, private facilities were often better equipped than public ones [37] . Reliable and accessible diagnostic services are paramount to SAO treatment, from cross-matching blood products, to safely titrating anesthetics, to using histopathology to determine disease type and treatment [1] .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found that many women and newborns are not stabilized prior to transport; many are discharged or referred with no follow-up plan (16). A mixed-methods study related to surgical capacity in Uganda reported on the common occurrence of women in obstructed labor receiving medication, but not being directed or escorted to a particular facility and left to coordinate their own transport (18). A report from Mexico documented cases of critically ill newborns transported without medical personnel present (19).…”
Section: What Is Referral Without a System? Just A Recommendationmentioning
confidence: 99%